Exploring loyalty of generation X in a retail store context - Pavlić, Ivana, ekonomistica (Array, 2021)
Despite the increased interest in consumers pertained to Generation X, there is still much that is not understood about this particular market segment. In particular, this refers to their retail-related behaviour as well as the satisfaction and loyalty of customers in traditional brick and mortar retail environment. The purpose of this paper is to expand the knowledge base about Generation X"s retail store attitudes and retail behaviour in order to identify their loyalty in a retail store context. For that reason, an empirical research was carried out using a convenience sample of 153 Generation X members from the Dubrovnik- Neretva County during the period from June 1 to October 1, 2016. To analyse the data, ordinal logistic regression and ANOVA methods were used. The results revealed that several variables were found partially statistically significant, i.e. retail service quality, retail store quality, product price, product assessment, retail store format and frequency of purchase. This paper provides a framework for an improved understanding of Generation X as consumers and their overall store experience. Moreover, it contributes to the existing literature by providing new insights into the loyalty of Croatian Generation X consumers.